2020
DOI: 10.1007/s13659-020-00275-9
|View full text |Cite
|
Sign up to set email alerts
|

Hordatines as a Potential Inhibitor of COVID-19 Main Protease and RNA Polymerase: An In-Silico Approach

Abstract: Total 40 natural compounds were selected to perform the molecular docking studies to screen and identify the potent antiviral agents specifically for Severe Acute Respiratory Syndrome Coronavirus 2 that causes coronavirus disease 2019 (COVID-19). The key targets of COVID-19, protease (PDB ID: 7BQY) and RNA polymerase (PDB ID: 7bV2) were used to dock our target compounds by Molecular Operating Environment (MOE) version 2014.09. We used 3 different conformations of protease target (6M0K, 6Y2F and 7BQY) and two d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Different software tested the interaction between the tested compounds and the binding site through physics-based equations used to calculate their binding affinities (Sliwoski et al, 2014 ). SARS-CoV-2 proteins, particularly proteases and spike proteins (Prajapat et al, 2020 ), have been targeted in many docking investigations hoping to understand the key amino acids essential for the interactions at the active site in SARS-CoV-2 (Calligari et al, 2020 ; Dahab et al, 2020 ; Khan et al, 2020 ; Kumar et al, 2020 ; Mohammad et al, 2020 ; Wu et al, 2020 ; Jairajpuri et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different software tested the interaction between the tested compounds and the binding site through physics-based equations used to calculate their binding affinities (Sliwoski et al, 2014 ). SARS-CoV-2 proteins, particularly proteases and spike proteins (Prajapat et al, 2020 ), have been targeted in many docking investigations hoping to understand the key amino acids essential for the interactions at the active site in SARS-CoV-2 (Calligari et al, 2020 ; Dahab et al, 2020 ; Khan et al, 2020 ; Kumar et al, 2020 ; Mohammad et al, 2020 ; Wu et al, 2020 ; Jairajpuri et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rosmarinic acid compound, the main ingredient of O. aristatus based on in-silico studies, can inhibit COVID-19 (Sarkar and Das, 2020;Wondmkun and Mohammed, 2020;Sampangi-crowdedah et al, 2019). The potential of other compounds in O. aristatus as an inhibitor of COVID-19 is sinensetin, cirsimaritin, 1,8-cineole, sagerinic acid, caffeic acid derivatives, and β-caryophyllene (Rowaiye et al, 2020;Sekiou et al, 2020;Sharma and Kaur, 2020;Dahab et al, 2020;Adem et al, 2020;Narkhede et al, 2020). Other studies have reported the effects of sinensetin, caffeic acid, limonene, 1,8-cineol, eugenol, and aurantiamide compounds as anti-influenza viruses (Shin et al, 2012;Li et al, 2020;Utsunomiya et al, 2014;Nagy et al, 2018;Li et al, 2016;Choi, 2018;Dai et al, 2013;Zhou et al, 2017).…”
Section: Research Articlementioning
confidence: 99%
“…Pada masa pandemi Covid-19 penemuan senyawa atau tanaman obat tradisional yang berpotensi sebagai antivirus dan imunomodulator terus dilakukan dan berdasarkan hasil penelitian senyawa yang terkandung dalam tanaman kumis kucing berpotensi sebagai inhibitor Covid-19 (Sarkar & Das ;Rowaiye et al, 2020;Sekiou et al, 2020;Adem et al, 2020;Dahab et al, 2020;Narkhede et al, 2020;Sharma & Kaur, 2020;Faramayuda et al, 2021), antiherpetik (Ikeda et al, 2011;Medini et al, 2016;Astani et al, 2011;Astani & Schnitzler, 2014;Bourne et al, 1999;Benencia & Courreges, 2000;Sharifi-Rad et al, 2018), anti-human immunodeficiency virus (HIV) (Lin et al, 1999;McDougall et al, 1998;Zhang et al, 2014;Mengoni et al, 2002;Kashiwada et al, 1998;Xu et al, 1996), anti hepatitis (Haid et al, 2012;Duan et al, 2016;Kong et al, 2013;Chang et al, 2016) dan imunomodulator (Harun et al, 2015;Woottisin et al, 2011;Friedman, 2015;Kim et al, 2008;Takano et al, 2004;Sanbongi et al, 2004;Youn et al, 2003).…”
Section: Pendahuluanunclassified